A novel hydraulic biogas digester controlling the scum formation in batch and semi-continuous tests using banana stems. (August 2019) - Pan, Shiyou; Wen, Chuan; Liu, Qiangqiang; Chi, Yue; Mi, Huizhi; Li, Zhenchong; Du, Liqin; Huang, Ribo; Wei, Yutuo
Graphical abstract: Highlights: A novel hydraulic digester with the ability to control scum formation was developed. Improved biogas yield and feedstock degradation were achieved in conical digesters. The conical shapes increased the diversity and evenness of the archaea community. The digester was operated in batch and continuous modes. Abstract: Scum formation is a widespread phenomenon and causes serious damage in straw biogas digesters. A 10-L novel hydraulic conical digester for controlling scum was developed in this work and compared with a hydraulic cylindrical digester that simulated the conventional digester. After 30 d of batch and 120 d of semi-continuous fermentations using banana stems, the scum volumes of in cylindrical digesters were 4.12 and 2.12 times that in the conical digesters, respectively. The conical digesters increased biogas production by 5.7% and 11.6% in batch and semi-continuous tests, respectively. The VS removal of feedstock in conical digesters were 5.6 and 7.2% greater than for the batch and semi-continuous cylindrical, respectively. The microbial diversity and evenness were higher in conical than cylindrical digesters. The results demonstrated that conical shape was an effective structure for controlling scum formation and improving biogas production.